CRM fundamentals - Kostojohn, Scott; Johnson, Mathew; Paulen, Brian (Apress, 2011)
"CRM fundamentals describes how to successfully build and execute a customer relationship management system, from managing the initial implementation to maintaining and evolving the program over time. It willhelp you identify goals, line up the right people, plan projects, and choose software packages and consultants. " -- Zadní strana obálky
Pravděpodobné místo vydání převzato z www stránek vydavatele
Obsahuje rejstřík
Keywords: řízení vztahů se zákazníky; podnikové informační systémy; implementace softwaru; customer relationship management; management information systems; software implementation; příručky; handbooks, manuals, etc